Cohesive Devices Analysis: Mind Your Writing Texture! - Luthfi Awwalia; Suhardi Suhardi (Makassar State University, 2020)
Writing ability is one of the most important yet difficult skill to be mastered. It has many components to make the good writing. The problematic aspect is to deal with lexical cohesive devices in general. This issue is being concerned especially for those who are going to take an IELTS Academic test. This study aims to examine the most lexical cohesive devices used by Undergraduate students in Yogyakarta, Indonesia. There are some researchers who conducted research on this field, on the other hand, this phenomenon is not a common topic discussed in Indonesia. Document analysis was done and accompanied by the interview in conducting this research. The respondents of this research were 14 who were willing to do the IELTS writing task 2 and being interviewed. The document analysis was conducted for students’ writing of IELTS writing Task 2. The result indicated that the most undeniable difficulty by the test-takers in the use of lexical cohesive devices was repetition. The lack of vocabulary was the main reason for the respondents, especially for the academic words. All test-takers could repeat the same words as many as 602 times. Hence, the impact of this research would enlighten the readers and the tutors to pay more attention to the use of lexical devices in writing.